Biocomputing 2007 : Proceedings of the Pacific Symposium. - Altman, Russ (World Scientific Publishing Company, 2006)
The Pacific Symposium on Biocomputing (PSB) 2007 is an international, multidisciplinary conference for the presentation and discussion of current research in the theory and application of computational methods in problems of biological significance. Presentations are rigorously peer reviewed and are published in an archival proceedings volume. PSB 2007 will be held January 3-7, 2007 at the Grand Wailea, Maui. Tutorials will be offered prior to the start of the conference. PSB 2007 will bring together top researchers from the US, the Asian Pacific nations, and around the world to exchange resea.